2008
DOI: 10.1016/j.bbr.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urokinase-type plasminogen activator in the acquisition, expression and reinstatement of cocaine-induced conditioned-place preference

Abstract: a b s t r a c tCocaine and many other psychostimulants strongly induce urokinase-type plasminogen activator (uPA) expression in the mesolimbic dopaminergic pathway, which plays a major role in drug-mediated behavioral plasticity [Bahi A, Boyer F, Gumy C, Kafri T, Dreyer JL. In vivo gene delivery of urokinase-type plasminogen activator with regulatable lentivirus induces behavioral changes in chronic cocaine administration. Eur J Neurosci 2004;20:3473-88; Bahi A, Boyer F, Kafri T, Dreyer JL. Silencing urokinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 72 publications
(130 reference statements)
2
7
0
Order By: Relevance
“…In addition, continuous unlimited access procedures are also more appropriate to study the pharmacological effects of compounds with long elimination half-lives, such as B428, in rodents and other small animals 25,39. Along these lines, a previous study from our laboratory has shown that in Wistar rats, B428 blocked cocaine-induced psychomotor stimulation 21. In agreement with the current findings, we have also shown in a previous study that ethanol treatment dose-dependently induced the expression and the enzymatic activity of another serine protease, namely, tissue plasminogen activator (tPA), in the NAc 32.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, continuous unlimited access procedures are also more appropriate to study the pharmacological effects of compounds with long elimination half-lives, such as B428, in rodents and other small animals 25,39. Along these lines, a previous study from our laboratory has shown that in Wistar rats, B428 blocked cocaine-induced psychomotor stimulation 21. In agreement with the current findings, we have also shown in a previous study that ethanol treatment dose-dependently induced the expression and the enzymatic activity of another serine protease, namely, tissue plasminogen activator (tPA), in the NAc 32.…”
Section: Discussionsupporting
confidence: 93%
“…B428 is a uPA inhibitor, which, when administered at lower doses, has been proven to selectively reduce the activity of uPA in rodents 2125. Given the reports that suggest that alcohol intake and alcoholism could be mediated by their interaction with serine proteases activity,26 and considering that some of the behavioral effects of psychostimulants depend on the levels of uPA activity,18,19,21 we hypothesized that by reducing the uPA activity, B428 will decrease alcohol consumption, and ethanol-induced CPP will be prevented.…”
Section: Introductionmentioning
confidence: 99%
“…Viral vector generation was obtained by cotransfection of HEK293T cells by the calcium phosphate method on 10-cm plates with 20 mg of pTK431, 15 mg of pDNRF, and 5 mg of pMDG-VSV-G. The supernatant was harvested 24 and 72 h after infection and viral particles were purified by ultracentrifugation (Bahi et al, 2005(Bahi et al, , 2008b.…”
Section: Lentiviral Constructions and Productionmentioning
confidence: 99%
“…Thus once place preference had been established, and the preference extinguished, reinstatement induced by a priming dose of cocaine is facilitated by uPA. Furthermore, lentivirus-mediated overexpression of uPA induces cocaine-, but not amphetamine-mediated behavioral changes, whereas, in contrast, tPA-overexpressing animals displayed greater place preference when administered amphetamine or morphine compared to uPA-overexpressing animals [149][150][151]. The behavioral effects are suppressed when tPA has been silenced using specific siRNAsexpressing lentiviruses.…”
Section: Drug Addictionmentioning
confidence: 82%
“…Lentiviral-mediated overexpression of uPA in the VTA induces doxycycline-dependent expression of its receptor, uPAR, but not its inhibitor, plasminogen activator inhibitor-1 (PAI-1) [149]. Local injection of uPA-specific siRNAs expressing lentiviruses into the ventral tegmental area suppressed cocaine-induced behavioral changes associated with uPA expression [149,150] Lentivirus-mediated overexpression of uPA in the Accumbens shell significantly augments cocaine-induced place preference, whereas its inhibition abolished the acquisition but not the expression of cocaine-induced place preference [149,150]. Furthermore, while this overexpression did not affect the ability of preference to be extinguished, reinstatement with a low dose of cocaine produced significantly greater preference to the cocaine-associated context.…”
Section: Drug Addictionmentioning
confidence: 98%